Kajian Visual Iklan Layanan Masyarakat Kesehatan Gigi Pepsodent 1995–2023: Perspektif Semiotika Dan Estetika Postmodern - Yosef Yulius; Hestia Rachmat Nunciata Lubis; Didiek Prasetya; Yohanes Reno; Valentinus Verdianto (Besaung : Jurnal Seni Desain dan Budaya, 2025)
This study examines the aesthetic values in Pepsodent Dental Health Public Service Advertisements (PSAs) from 1995 to 2023. The main focus of the study is to analyze how these PSAs maintain their visual identity, message consistency, and cultural relevance amidst technological and media developments. Using a qualitative descriptive approach, this study dissects the visual and verbal communication strategies in each PSA period. The theoretical framework is based on Dharsono Sony Kartika's Postmodern aesthetic theory, with an analysis of visual form and special form, and supported by Ferdinand de Saussure's semiotic approach to examine the relationship between signifiers and signifieds in media texts. The results show that these PSAs consistently maintain key elements such as the iconic tooth character, toothbrush, toothpaste, children as the primary audience, and dentists as representatives of health authorities, supported by the jingle lyrics that remain the same. The visual transformation from 2D to 3D animation, to the use of human actors and animal mascots, demonstrates creative adaptation to changes in audiences and distribution media. This study concludes that the Pepsodent Dental Health PSA is an example of successful long-term visual communication that is able to combine traditional-based health messages with a contemporary aesthetic approach, and is effective in building public awareness of the importance of maintaining dental health through media that is attractive, communicative, and relevant across generations.